Answer:6/36
Step-by-step explanation:
Answer:
dont know if this is correct
In the Triangle ABD, Using Pythagoras theorem we can write
![AB^2=BD^2+AD^2\\ \\ AB^2=9^2+y^2\\ \\ AB^2=81+y^2\\ \\](https://tex.z-dn.net/?f=%20AB%5E2%3DBD%5E2%2BAD%5E2%5C%5C%20%5C%5C%20AB%5E2%3D9%5E2%2By%5E2%5C%5C%20%5C%5C%20AB%5E2%3D81%2By%5E2%5C%5C%20%5C%5C%20)
In the Triangle ACD using Pythagoras Theorem
![AC^2=AD^2+CD^2\\ \\ AC^2=y^2+7^2\\ \\ AC^2=y^2+49\\](https://tex.z-dn.net/?f=%20AC%5E2%3DAD%5E2%2BCD%5E2%5C%5C%20%5C%5C%20AC%5E2%3Dy%5E2%2B7%5E2%5C%5C%20%5C%5C%20AC%5E2%3Dy%5E2%2B49%5C%5C%20%20)
Now in the larger Triangle ABC, we can write
![AB^2+AC^2=BC^2](https://tex.z-dn.net/?f=%20AB%5E2%2BAC%5E2%3DBC%5E2%20)
Now substitute the values from the above equations we get
![81+y^2+49+y^2=(9+7)^2\\ \\ 130+2y^2=16^2\\ \\ 130+2y^2=256\\ \\ 65+y^2=128\\ \\ y^2=128-65=63\\ \\ y=\sqrt{63} =3\sqrt{7} \\](https://tex.z-dn.net/?f=%2081%2By%5E2%2B49%2By%5E2%3D%289%2B7%29%5E2%5C%5C%20%5C%5C%20130%2B2y%5E2%3D16%5E2%5C%5C%20%5C%5C%20130%2B2y%5E2%3D256%5C%5C%20%5C%5C%2065%2By%5E2%3D128%5C%5C%20%5C%5C%20y%5E2%3D128-65%3D63%5C%5C%20%5C%5C%20y%3D%5Csqrt%7B63%7D%20%3D3%5Csqrt%7B7%7D%20%5C%5C%20)
Answer:
Step-by-step explanation:
(a+b)² = a² + 2ab + b²
The only choice that has the form a² + 2ab + b² is D.
Answer:
2(30+x)
Step-by-step explanation:
![55+2x+5\\=60+2x\\=2(x+30) or 2(30+x)](https://tex.z-dn.net/?f=55%2B2x%2B5%5C%5C%3D60%2B2x%5C%5C%3D2%28x%2B30%29%20or%202%2830%2Bx%29)